Artificial Intelligence (AI) and Automation in Human Resources : Shifting the Focus from Routine Tasks to Strategic Initiatives for Improved Employee Engagement - Sundari, Sri; Silalahi, Verry Albert Jekson Mardame; Wardani, Febri Pramudya; Siahaan, Rahel Sintadevi; Sacha, Shinta; Krismayanti, Yanti; Anjarsari, Nisa (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study examines how implementing artificial intelligence (AI) in human resource management (HR) impacts employee engagement and operational efficiency. By automating tasks like data management, scheduling, and payroll, AI enables HR teams to focus on strategic initiatives such as talent management and culture development. Using a descriptive qualitative approach and literature review, the research finds that AI adoption improves operational efficiency by 30% and enhances employee engagement through personalized experiences and real-time feedback. Additionally, AI supports better strategic decision-making with predictive employee data analysis. However, challenges include employee resistance and the need for HR retraining. For optimal results, companies should strengthen internal communication and establish supportive policies that enhance engagement and well-being through AI integration.